2009
DOI: 10.1016/j.jneuroim.2009.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Viral nanoparticles associate with regions of inflammation and blood brain barrier disruption during CNS infection

Abstract: Targeted treatment of inflammatory diseases of the central nervous system (CNS) remains problematic due to the complex pathogenesis of these disorders and difficulty in drug delivery. The plant virus, cow pea mosaic virus (CPMV), has recently been explored as a nanoparticle delivery system for therapeutics targeting a number of diseases including cancer and neurodegeneration. To understand the biodistribution of CPMV in the CNS, we examined CPMV uptake during infection of mice with neurotropic mouse hepatitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…This study demonstrated that, unlike other VNPs we have tested [14,44,45,47,48], unmodified HK97 PII particles have a remarkably low propensity to interact with tumor cells and are thus an attractive platform for subsequent targeting strategies. Particles specifically designed for cell targeting applications were prepared by a combination of genetic and chemical modification.…”
Section: Resultsmentioning
confidence: 89%
“…This study demonstrated that, unlike other VNPs we have tested [14,44,45,47,48], unmodified HK97 PII particles have a remarkably low propensity to interact with tumor cells and are thus an attractive platform for subsequent targeting strategies. Particles specifically designed for cell targeting applications were prepared by a combination of genetic and chemical modification.…”
Section: Resultsmentioning
confidence: 89%
“…In the push for new approaches, recent developments have turned towards nanotechnology, and several promising examples of plant viruses, such as cowpea mosaic virus (CPMV), hibiscus chlorotic ringspot virus (HCRSV), red clover necrotic mosaic virus (RCNMV), and the bacteriophages Hong Kong 97 (HK97) and M13 have emerged for applications for cancer treatment including molecular detection, targeting and trafficking (Steinmetz, 2010;Yildiz et al, 2011). Although some viruses, such as CPMV and canine parvovirus (CPV), exhibit a natural affinity for a particular type of cell Shriver et al, 2009;Leong et al, 2010), cellular uptake is often inefficient. By making use of the reactive lysine, cysteine, aspartic acid and glutamic acid groups, the outer surface of the virus capsid can be made accessible to both genetic engineering and chemical modification strategies such as N-hydroxysuccinimide coupling, Michael addition to maleimides and carbodiimide activation (Steinmetz, 2010).…”
Section: Viruses For the Treatment Of Cancermentioning
confidence: 99%
“…The engineering of this signaling peptide would help to generate more powerful tools in crossing BBB. Additionally, because the viral infection to the brain often associates with neuroinflammation and BBB disruption, people have also proposed to employ other types of virus-based nanodelivery system that could disrupt the BBB to enhance the drug targeting into the brain (Shriver et al 2009). The use of neurotrophic virus during brain drug delivery greatly enhanced the BBB permeability as well as the drug delivery into the brain.…”
Section: Different Routes For Brain Drug Delivery With Nanotechnologymentioning
confidence: 99%